The effect of increasing the coinsurance rate on outpatient utilization of healthcare services in South Korea - Hyo Jung Lee; Sung-In Jang; Eun-Cheol Park (BMC, 2017)
Abstract Background The Korean healthcare system is composed of costly and inefficient structures that fail to adequately divide the functions and roles of medical care organizations. To resolve this matter, the government reformed the cost-sharing policy in November of 2011 for the management of outpatients visiting general or tertiary hospitals with comparatively mild diseases. The purpose of the present study was to examine the impact of increasing the coinsurance rate of prescription drug costs for 52 mild diseases at general or tertiary hospitals on outpatient healthcare service utilization. Methods The present study used health insurance claim data collected from 2010 to 2013. The study population consisted of 505,691 outpatients and was defined as those aged 20-64 years who had visited medical care organizations for the treatment of 52 diseases both before and after the program began. To examine the effect of the cost-sharing policy on outpatient healthcare service utilization (percentage of general or tertiary hospital utilization, number of outpatient visits, and outpatient medical costs), a segmented regression analysis was performed. Results After the policy to increase the coinsurance rate on prescription drug costs was implemented, the number of outpatient visits at general or tertiary hospitals decreased (β = −0.0114, p < 0.0001); however, the number increased at hospitals and clinics (β = 0.0580, p < 0.0001). Eventually, the number of outpatient visits to hospitals and clinics began to decrease after policy initiation (β = −0.0018, p < 0.0001). Outpatient medical costs decreased for both medical care organizations (general or tertiary hospitals: β = −2913.4, P < 0.0001; hospitals or clinics: β = −591.35, p < 0.0001), and this decreasing trend continued with time. Conclusions It is not clear that decreased utilization of general or tertiary hospitals has transferred to that of clinics or hospitals due to the increased cost-sharing policy of prescription drug costs. This result indicates the cost-sharing policy, intended to change patient behaviors for healthcare service utilization, has had limited effects on rebuilding the healthcare system and the function of medical care organizations.